Planerski in/ali projektantski pristop k urejanju javnega mestnega prostora s primeri trgov na Hrvaškem - Jukić, Tihomir (Urbani izziv, 1999)
Faced with problems regarding the organisation of public city areas, the authors of this text undertook practical, concrete exercises on typologically differing squares. The projects had reached different levels of treatment, from competition proposals to construction and controle of execution. Based on practical experience they recapitulated their practical experience and by determining the basic elements of these projects selectively determined the level of their influence on final decisions. Seven proposals for design of squares - public open spaces are presented.
Keywords: Croatia; Hrvatska; mesta; prostorsko urejanje; trgi (urbanizem); urbanism; urbanizem